2018
DOI: 10.1055/a-0657-3905
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for B-Mode Ultrasound (US) Evaluation of the Plantar Aponeurosis (PA) Thickness in Healthy Subjects

Abstract: · Abd Ellah MM, Kremser C, Strobl S et al. New Approach for B-Mode Ultrasound (US) Evaluation of the Plantar Aponeurosis (PA) Thickness in Healthy Subjects. Fortschr Röntgenstr 2018; DOI: 10.1055/a-0657-3905.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The relative reliability of thickness and echogenicity measurement of the plantar fascia was proven to be high (interclass correlation coefficient, ICC = 0.88) [401]. Good reproducibility was also found (intra-and interrater reliability, ICC > 0.821, ICC> 0.849) [402], as well as good agreement between an experienced and a novel sonographer [403]. In another study the intra-tester reliability was shown to significantly surpass the inter-tester reliability in plantar fasciitis (0.89 vs. 0.61, respectively) [404].…”
Section: Clinical Applicationmentioning
confidence: 84%
“…The relative reliability of thickness and echogenicity measurement of the plantar fascia was proven to be high (interclass correlation coefficient, ICC = 0.88) [401]. Good reproducibility was also found (intra-and interrater reliability, ICC > 0.821, ICC> 0.849) [402], as well as good agreement between an experienced and a novel sonographer [403]. In another study the intra-tester reliability was shown to significantly surpass the inter-tester reliability in plantar fasciitis (0.89 vs. 0.61, respectively) [404].…”
Section: Clinical Applicationmentioning
confidence: 84%